Contradictory Speech in the Dialogue of Teddy Soeraatmadja's Lovely Man Film - Siyam, Sahrul; Rustono, Rustono; Haryadi, Haryadi (Universitas Negeri Semarang, 2024)
This study examines the contradictory speech between the two main characters in the film